The roles of history: age and prior exploitation in aquatic container habitats have immediate and carry‐over effects on mosquito life history. (5th July 2017) - WESTBY, KATIE M.; JULIANO, STEVEN A.
Abstract : 1. Per‐capita resource availability in aquatic habitats is influenced directly by consumer density via resource competition and indirectly via delayed resource competition when temporally non‐overlapping cohorts of larvae exploit the same resources. In detritus‐based systems, resources are likely to be influenced by the age of the aquatic habitat, as detritus changes in quality over time and may be replenished by new inputs. 2. For aquatic insects that exploit detritus‐based habitats, feeding conditions experienced during immature stages can influence fitness directly via effects on development and survivorship, but also indirectly by influencing adult traits such as fecundity and longevity. 3. Larval habitat age and prior resource exploitation were manipulated in a field experiment using the container mosquito Aedes triseriatus . 4. It was found that A. triseriatus from older habitats had greater larval survival, faster development and greater adult longevity. Exploitation of larval habitats by a prior cohort of larvae had a significant negative effect on subsequent cohorts of larvae by delaying development. 5. It is suggested that extended conditioning of detritus probably resulted in conversion of recalcitrant resources to more available forms which improved the quality of the habitat. 6. In a parallel study, evidence was found of carry‐over effects of habitat age and prior exploitation on adult longevity for A. triseriatus and Aedes japonicus collected from unmanipulated aquatic habitats. 7. These results indicate the importance of detritus dynamics and the discontinuous nature of resource competition in these mosquito‐dominated aquatic systems. Abstract : Aquatic container habitats vary greatly in age and their history of use by prior non‐overlapping cohorts of detritivorous mosquito larvae. In this study habitat age and prior use by larvae were manipulated. It was found that more larvae survived, they developed faster, and the resulting adults lived longer when reared in older habitats. It was also found that prior utilisation delayed development in the younger habitats. It is hypothesised that extended conditioning of leaf detritus increased the availability of recalcitrant nutrients, making older habitats of higher quality. Prior utilisation probably only has strong effects in poor‐quality habitats.